Mitochondrial Dynamics Decrease Prior to Axon Degeneration Induced by Vincristine and are Partially Rescued by Overexpressed cytNmnat1 - Berbusse, Gregory W.; Woods, Laken C.; Vohra, Bhupinder P. S.; Naylor, Kari (Frontiers in Cellular Neuroscience, 2016)
Axon degeneration is a prominent feature of various neurodegenerative diseases, such as Parkinson’s and Alzheimer’s, and is often characterized by aberrant mitochondrial dynamics. Mitochondrial fission, fusion, and motility have been shown to be particularly important in progressive neurodegeneration. Thus we investigated these imperative dynamics, as well as mitochondrial fragmentation in vincristine induced axon degradation in cultured dorsal root ganglia (DRG) neurons. CytNmnat1 inhibits axon degeneration in various paradigms including vincristine toxicity. The mechanism of its protection is not yet fully understood; therefore, we also investigated the effect of cytNmnat1 on mitochondrial dynamics in vincristine treated neurons. We observed that vincristine treatment decreases the rate of mitochondrial fission, fusion and motility and induces mitochondrial fragmentation. These mitochondrial events precede visible axon degeneration. Overexpression of cytNmnat1 inhibits axon degeneration and preserves the normal mitochondrial dynamics and motility in vincristine treated neurons. We suggest the alterations in mitochondrial structure and dynamics are early events which lead to axon degeneration and cytNmnat1 blocks axon degeneration by halting the vincristine induced changes to mitochondrial structure and dynamics.